A Proposed Teaching Model In The Diversity Of Teaching And Its Effect On The Achievement And Chemical Culture Of Secondary School Students - Ameer Abbood, Suhad Abdul (Opción, 2019)
The aim of research is to found out the effect of a proposed teaching model on the diversity of teaching in the achievement and chemical culture of a sam- ple of fifth class scientist (bio) students. The sample consisted of (69) students randomly distributed to the first two experimental groups (34) students stud- ied proposal of the proposed teaching model, and the second control group studied in the normal method which consists (35) students. It had equivalence in variables (memory, absorption, application and analysis), the researcher prepared the first two tests according to Bloom’s classification, consisting of (40) paragraphs, and the second is the chemical culture test (20). The results of the study showed there were significant differences in achievement and chem- ical culture for the benefit of the experimental group studied according to the proposed teaching model. The results of the research, that recommended the use of the proposed teaching model for the diversity teaching and its impact on the achievement and chemical culture because of its great importance in increasing the scientific knowledge and scientific achievement of the students..